Pluvial flooding in urban areas across the European continent - Prokic, Marija Nebojsa; Savić, Stevan; Pavić, Dragoslav (Geographica Pannonica, 2019)
Pluvial flooding is a result of overland flow and ponding before the runoff enters any watercourse, drainage system or sewer, or cannot enter it because the network is full to capacity, usually caused by intense rainfall. River and coastal floods get the most attention since they are largest and last the longest, while pluvial floods are relatively marginalized in research. Therefore, the main goal of this research was to show risk posed by pluvial floods, their connection to current global climate change processes, present effects of flooding in European cities, as well as what we can expect in the future. Furthermore, the aims were to present and get more familiar with scientific projects, strategies, directives and measures devised both on national and international levels, that deal with urban pluvial flood issues across the European continent. Climate change projections indicate that there will be an increase in the frequency and intensity of rainfall events throughout Europe and along with ongoing urbanization, the problem of pluvial flooding will most certainly require more attention, which it is starting to receive. Some countries have already developed their strategies and initiatives and implemented both structural and non-structural measures, such as spatial planning, constructional measures, information systems, reducing land sealing through policies, building codes and standards, on-site improvement of retention, infiltration, evaporation, and rainfall water recycling with the use of green roofs, permeable or porous pavements, rain gardening or urban rainwater harvesting. At the same time, there are numerous research papers, studies, conferences and workshops devoted to the problem of pluvial flooding and its management carried out in an attempt to properly deal with this hazard.